Evaluation Of Port Landside Facilities To Support Operational Activities At Tanjung Kalian Ferry Port In Province of Bangka Belitung Islands - Widjatmoko, Eko Nugroho; Yulianto, Andri; Priyono, Broto; Guntoro Zain Ma`Rif; Ahyani, Ahyani; Dita Rama Insyanda (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
Increasing interconnectedness of economic and social activities in a region increases the need for an effective and efficient transportation system. The success of regional development is highly dependent on the role of transportation as the various fields such as economy, social, culture, and security. Smooth flow of passengers and goods can improve the regional economy and facilitate regional development. Tanjung Kalian Ferry Port, located in Bangka Belitung Islands Province, is one of the important ports in supporting the mobilization of goods and passengers between the region and South Sumatra Province. However, operation of this port still experiences various problems such as irregular traffic flow and cargo handling due to suboptimal land facilities. This research is expected to provide comprehensive recommendations to improve efficiency and effectiveness of services and optimize control and port operations as to create a safe, secure, organized, and comfortable port area for the community and users.